Quality of mental health services and rights of people receiving treatment in inpatient services in Finland: a cross-sectional observational survey with the WHO QualityRights Tool Kit - Lantta Tella; Anttila Minna; Välimäki Maritta (United Kingdom, 2022)
Background: This article aims to review the quality of mental health services and the rights of the people receiving treatment in inpatient hospital care in Finland using the World Health Organization's QualityRights Tool Kit as a part of a randomized controlled trial VIOLIN. So far, reports on the QualityRights Tool Kit have mainly been from low- and middle-income countries or countries lacking resources for health services. Reports from countries with well-resourced health care systems, such as the Nordic countries, are still quite few.
Methods: A cross-sectional observational survey was conducted on 13 closed inpatient psychiatric wards (acute, rehabilitation, forensic psychiatric) at eight hospitals in Finland. The data for the survey were gathered through a document review, observations, and group interviews among staff members, service users and family members. The STROBE checklist for cross-sectional studies was followed in the reporting.
Results: Finnish mental health services are partially or fully achieving the standards set by the WHO QualityRights Tool Kit (final scores: 2.5-2.9 out of 3). The highest final score out of the five themes (2.9/3) was achieved under Freedom from torture or cruel, inhuman or degrading treatment or punishment and from exploitation, violence and abuse. The lowest final score out of the five themes (2.5/3) was achieved under the right to exercise legal capacity and the right to personal liberty and the security of person.
Conclusions: According to the findings, Finnish mental health services appear to be of high quality. However, we have identified some gaps in quality, which we have addressed in a national randomized controlled trial VIOLIN. Improvements can be realized through shared decision making and relaying information to service users.